The Kenyan assistive technology ecosystem: a network analysis - Emma M. Smith; Stephanie Huff; Rose Bukania; Bernard Chiira; Catherine Holloway; Malcolm MacLachlan (Global Health Action)
Background Assistive technology is central to the realization of the rights of persons with disabilities. However, there remains limited access to assistive technology throughout much of the world, with particularly poor access in lower- and middle-income countries. Evaluating stakeholder engagement in assistive technology networks has been used as a successful strategy to understand and address gaps in the assistive technology ecosystem. Objective The objective of this research was to provide an overview of the Kenyan Assistive Technology Ecosystem, including available assistive products and related services, and an understanding of the nature and strength of relationships between stakeholders Methods In this study, we employed an online qualitative stakeholder survey (2021) with representatives of organizations involved in assistive technology in Kenya. Results The assistive technology network in Kenya is distributed, with Government Ministries and Agencies and Organizations of persons with disabilities central to the network. The strength of relationships is concentrated on awareness and communication, with fewer organizations actively collaborating. Innovation training organizations are not yet well integrated into the network. Conclusions Improving access to assistive technology in Kenya will benefit from greater collaboration amongst all assistive technology stakeholders.